GENDER DIFFERENCES IN THE MANIFESTATION OF COMMUNICATIVE COMPETENCE OF BOYS AND GIRLS - N. K. Buvalets (Science and Innovation Center Publishing House, 2019)
The article studies the communicative competence of boys and girls, which plays an important role in the ability to build favorable and successful interpersonal relationships with each other.